2022
DOI: 10.3389/fmats.2022.944368
|View full text |Cite
|
Sign up to set email alerts
|

Combustion and Thermal Properties of Flame Retardant Polyurethane Foam With Ammonium Polyphosphate Synergized by Phosphomolybdic Acid

Abstract: Phosphomolybdic acid (PMA) as a synergist was added into polyurethane (PU) rigid foam with ammonium polyphosphate (APP) to improve its flame retardancy and thermal stability. The combustion performance of PU was studied by limiting oxygen index (LOI), UL-94, and a cone calorimeter. The thermal degradation behavior of PU was determined by thermogravimetric analysis (TG) and thermogravimetric infrared spectroscopy (TG-IR). Experimental results showed that the introduction of PMA could further improve the flame r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…The beginning of the emission of aromatic compounds from T max1a for ethyl formates 1-3 and T max1 ′ for methyl acetates 4-6 is well seen from the gaseous FTIR spectra, shown in Figure 4. Their emission is confirmed by the appearance of the stretching vibrations of the C Ar-H at 3050-3079 cm −1 , the stretching vibrations of the C Ar =C Ar at 1510-1580 cm −1 , and the out-of-plane deformation vibrations of the C Ar-H at 780-867 cm −1 [43][44][45]. The emission of aromatic fragments is visible to temperatures of 500-540 • C for all the tested compounds.…”
Section: Methodsmentioning
confidence: 70%
“…The beginning of the emission of aromatic compounds from T max1a for ethyl formates 1-3 and T max1 ′ for methyl acetates 4-6 is well seen from the gaseous FTIR spectra, shown in Figure 4. Their emission is confirmed by the appearance of the stretching vibrations of the C Ar-H at 3050-3079 cm −1 , the stretching vibrations of the C Ar =C Ar at 1510-1580 cm −1 , and the out-of-plane deformation vibrations of the C Ar-H at 780-867 cm −1 [43][44][45]. The emission of aromatic fragments is visible to temperatures of 500-540 • C for all the tested compounds.…”
Section: Methodsmentioning
confidence: 70%
“…Regarding the literature, the results achieved with these flame retardants were comparable to or higher than those presented in other works. For instance, Xu et al, 2022 [ 90 ], showed that a commercial PUF with 15% of APP loading only reached a V-1 rating. In other works, using phosphorous and silicon-based flame retardants for PUFs, they showed that it is sometimes necessary to either use a synergist or higher loadings to reach a V-0 rating [ 91 , 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…Polyurethane is an important polymer that can derive a variety of products, which is widely used in the market 1 . Polyurethane foam (PUF) is a polymer synthesized by polyols, isocyanates, and other additives, which is easy to prepare and has good mechanical properties, insulation, and other excellent properties 2 . PUF is widely used in construction, medical treatment, furniture, aviation, military, and other applications 3 .…”
Section: Introductionmentioning
confidence: 99%